Muturu cattle of western Nigeria. II. Survivability, reproductive and growth performances in an area of light Glossina palpalis density - Ferguson, W. (1967)
The performance Muturu cattle in a region of light Glossina palpalis density is investigated. Discussions and data on survivability, reproductivity, carcass yield and carcass composition included.